Penerapan Aplikasi “Bela Andin” untuk Pencegahan Pelecehan Seksual pada Anak Usia Dini - Safitri, Hana Ika; Auliya, Alfiana Falan Syarri; Fashlah, Anggita Gunati; Hasanah, Nur (LP2M IAIN Sultan Amai Gorontalo, 2026)
Sexual abuse cases involving young children remain a serious problem in Indonesia. Children are vulnerable to becoming victims due to their limited understanding of bodily boundaries, refusal skills, and courage to report abuse. This study aims to describe the process of implementing the “Bela Andin” application as an educational medium for the prevention of sexual abuse in young children using a qualitative approach. Data was obtained through interviews with teachers and documentation of the application's use in kindergarten classrooms. Data analysis was conducted in three stages: data reduction, data display, and conclusion drawing. The results of the study show that the “Bela Andin” application makes it easier for children to understand the concept of bodily boundaries and trains them to respond by refusing and reporting. Teachers assessed this application as practical, relevant to their needs, and capable of serving as a bridge for communication on sensitive topics. However, limitations in equipment, intensive assistance, and variations in digital literacy remain challenges. These findings confirm that the “Bela Andin” application is effective as an educational innovation for the prevention of sexual abuse of young children, but minor improvements to the application are needed.